Child health inequalities and its dimensions in Pakistan - Fowad Murtaza; Tajammal Mustafa; Rabia Awan (Journal of Family and Community Medicine, 2015)
Background and Objective: Poverty and inequality in health is pervasive in Pakistan. The provisions and conditions of health are very dismal. A significant proportion of the population (16.34%) of Pakistan is under 5 years, but Pakistan is in the bottom 5% of countries in the world in terms of spending on health and education. It is ranked the lowest in the world with sub-Sahara Africa in terms of child health equality. The objective of this study was to examine child health inequalities in Pakistan. Materials and Methods: We analyzed data from Pakistan Integrated Household Survey/Household Integrated Economic Survey 2001-2002, collected by the Pakistan Bureau of Statistics, Government of Pakistan. Coverage of diarrhea and immunization were used as indicators of child health. Stata 11.0 was used for data analysis. Descriptive statistics including frequency distribution and proportions for categorical variables and mean for continuous variables were computed. Results: Children under 5 years of age account for about 16.34% of the total population, 11.76% (2.5 million) of whom suffered from diarrhea in 1-month. The average duration of a diarrheal episode was 7 days. About 72% of the children who had diarrhea lived in a house without pipe-borne water supply. Around 22% children who had diarrhea had no advice or treatment. More than one-third of the households had no toilet in the house, and only 29% of the households were connected with pipe-borne drinking water. About 7.73% (1.6 million) children had never been immunized. The main reason for nonimmunization was parents′ lack of knowledge and of immunization. Conclusion: Child health inequalities in Pakistan are linked with several factors such as severe poverty, illiteracy, lack of knowledge, and awareness of child healthcare, singularly inadequate provision of health services, and poor infrastructure.